Antimicrobial biodegradable chitosan-based composite Nano-layers for food packaging - Pandey V.K.; Upadhyay S.N.; Niranjan K.; Mishra P.K. (My University, 2025)
Stable silver nanoparticles (AgNPs) of size 80 ± 11 nm produced by chitosan (CH) mediated green synthesis were blended with polyvinyl alcohol (PVA) to form electrospun fibrous composite nano-layers (FCNLs). The chitosan acted as the stabilising as well as an antimicrobial agent in combination with the AgNPs which were characterised using UV–visible spectrophotometry, dynamic light scattering (DLS) and scanning electron microscopy (SEM). The crystallinity and chemical nature of the electrospun composite was characterised by using X-ray diffraction (XRD) and FTIR spectroscopy, respectively, and its hydrophobicity was characterised by measuring the water contact angle. The electrospun composite showed effective antimicrobial activity against Listeria monocytogenes (gram +ve) and Escherichia coli (gram –ve) bacterial species. The electrospun composite, when tested as packaging material for meat, showed bio-activity and extended the meat shelf-life by one week. The electrospun nanocomposite is able to inhibit microbial degradation of packaged food and extend its keeping quality in an eco-friendly manner. © 2020 Elsevier B.V.